PEMBELAJARAN BAHASA DAN SASTRA DAERAH SEBAGAI WAHANA PENDIDIKAN KARAKTER BANGSA (LEARNING REGIONAL LANGUAGE AND LITERATURE AS A MEANS OF EDUCATION OF NATIONAL CHARACTER) - A. Syukur Ghazali (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2013)
AbstractLearning Regional Language and Literature as a Means of Education of NationalCharacter. Learning the language and literature to be a vehicle for cultural educationand the nation’s character is based on the view that language and literature has thepotential to become an institution that gives hope for people to talk about the ultimatereality of life. An imaginative literary works offer a rich selection of possibilities aboutthe structure of complex life. Michael Novak (Lickona, 1991: 50) states that the elementsforming the moral attitude can be traced to religious traditions, literature-based storiesof local culture (indegeneous), policy advice (sage), and a view of life that flows figureshereditary historically through discourse language and literature. More than that, themight of the local language as the medium of education has been proved empirically byIndia and Thailand who use writing as writing Hindi and Thai official. Even Singh(2010), an international seminar on retention native language, India explains that thestate establish a political idea, not a linguistically formulated Hindi language. Thisdesignation aims to make the “mother tongue Becomes a rallying point for groups ofpeople to unite and express their solidarity more as a political entity.” Therefore, theintention of the government to establish policies and conduct conservation programs inthe local language of each province, as well as through literature, is key to theimplementation of this idea.Keywords: literature as forming the moral stance, regional literature, governmentgoodwillAbstrakPembelajaran Bahasa dan Sastra Daerah sebagai Wahana Pendidikan KarakterBangsa. Pembelajaran bahasa dan sastra untuk menjadi wahana pendidikan budayadan karakter bangsa didasarkan pada pandangan bahwa bahasa dan sastra berpotensiuntuk menjadi institusi yang memberi harapan bagi manusia untuk berbicara tentangrealitas kehidupan yang hakiki. Karya sastra merupakan tawaran imajinatif yang kayadengan pilihan kemungkinan tentang struktur kehidupan yang kompleks. Michael Novak(Lickona, 1991: 50) menyatakan bahwa unsur pembentuk sikap moral bisa dilacakdari tradisi keagamaan, cerita sastra berbasis kebudayaan lokal (indegeneous), nasihatkebijakan (sage), dan pandangan hidup tokoh yang mengalir secara turun-temurunsecara historis melalui wacana bahasa dan sastra. Lebih dari itu, keperkasaan bahasadaerah sebagai medium pendidikan telah dibuktikan secara empirik oleh India danThailand yang menggunakan tulisan Hindi dan Thai sebagai tulisan resmi negara.Bahkan Singh (2010), dalam seminar internasional tentang pemertahanan bahasa ibu,menjelaskan bahwa negara India menetapkan gagasan politis, bukan merumuskanbahasa Hindi secara linguistik. Penetapan ini bertujuan untuk menjadikan “mother20tongue becomes a rallying point for group of people to unite and express their solidaritymore as a political entity”. Oleh karena itu, niat baik pemerintah untuk menetapkankebijakan dan melakukan program pelestarian bahasa daerah di wilayah propinsimasing-masing, juga melalui sastra, merupakan kunci bagi terlaksananya gagasanini.Kata-kata kunci: sastra sebagai pembentuk sikap moral, sastra daerah, niat baikpemerintah